Fungal His-Tagged Nitrilase from Gibberella intermedia: Gene Cloning, Heterologous Expression and Biochemical Properties - Gong, Jin-Song (Public Library of Science, 2012)
BACKGROUND: Nitrilase is an important member of the nitrilase superfamiliy. It has attracted substantial interest from academia and industry for its function of converting nitriles directly into the corresponding carboxylic acids in recent years. Thus nitrilase has played a crucial role in production of commercial carboxylic acids in chemical industry and detoxification of nitrile-contaminated wastes. However, conventional studies mainly focused on the bacterial nitrilase and the potential of fungal nitrilase has been far from being fully explored. Research on fungal nitrilase gene expression will advance our understanding for its biological function of fungal nitrilase in nitrile hydrolysis. METHODOLOGY/PRINCIPAL FINDINGS: A fungal nitrilase gene from Gibberella intermedia was cloned through reverse transcription-PCR. The open reading frame consisted of 963 bp and potentially encoded a protein of 320 amino acid residues with a theoretical molecular mass of 35.94 kDa. Furthermore, the catalytic triad (Glu-45, Lys-127, and Cys-162) was proposed and confirmed by site-directed mutagenesis. The encoding gene was expressed in Escherichia coli Rosetta-gami (DE3) and the recombinant protein with His(6)-tag was purified to electrophoretic homogeneity. The purified enzyme exhibited optimal activity at 45°C and pH 7.8. This nitrilase was specific towards aliphatic and aromatic nitriles. The kinetic parameters V (max) and K (m) for 3-cyanopyridine were determined to be 0.81 µmol/min·mg and 12.11 mM through Hanes-Woolf plot, respectively. 3-Cyanopyridine (100 mM) could be thoroughly hydrolyzed into nicotinic acid within 10 min using the recombinant strain with the release of about 3% nicotinamide and no substrate was detected. CONCLUSIONS/SIGNIFICANCE: In the present study, a fungal nitrilase was cloned from the cDNA sequence of G. intermedia and successfully expressed in E. coli Rosetta-gami (DE3). The recombinant strain displayed good 3-cyanopyridine degradation efficiency and wide substrate spectrum. This fungal nitrilase might be a potential candidate for industrial applications in carboxylic acids production.